Subjective Narrative: A Conceptual Approach to the Life History Method in the Context of Visual Arts Education - Raquimán-Ortega, Patricia (2020)
This article explores a conceptual framework that considers life histories as an approach to examining some ideas about Visual Arts teaching. This essay tries to expand the notion of the teaching and learning process, linking it to the vital environment to highlight daily life interpretation. From this point, this essay reflects on how the context in which teachers and students live becomes an opportunity to understand the near space and its relationships. With the support of life histories, narratives allow for closeness to their ways of reconstructing the experience in teaching the visual arts.